The Implementation of Merdeka Belajar Kampus Merdeka Policy: Students’ Awareness, Participation, and its Impact - Apoko, Tri Wintolo; Hendriana, Benny; Umam, Khoerul; Handayani, Isnaini; Supandi (LPPM Undiksha, 2022)
Learning outside the study program and campus is a learning option for students to improve the quality of graduates who can adapt to the industrial world at the national and international levels. This study aims to analyze the level of awareness and participation of students in the MBKM policy and its impact. The type of research used is a survey with descriptive analysis techniques. The subjects of this research were 11579 university students. The instrument used was a questionnaire consisting of two parts, namely the identity of the respondent and questions about the MBKM policy. The results of this study indicate that the level of student awareness of the MBKM policy is quite high, including the level of student participation. Meanwhile, the response to the impact of the MBKM policy on students was said to be high. This is based on the benefits of the MBKM program such as learning experience, recognition of 20 credits, and improvement of soft skills. Therefore, this MBKM policy has implications for increasing student participation in participating in learning activities outside the study program and campus to support Kemdikbudristek's Main Performance Indicator (IKU) 2. Thus, the findings of this study have several implications. First, the MBKM program will continue to be attended by students with great enthusiasm due to the high student awareness of the MBKM policy. Second, the quality of learning outside the campus will increase because student interest in participating in the MBKM program is quite large. Third, the sustainability of the MBKM program organized by the study program will run well. This is based on the benefits of the MBKM program which is able to provide many skills, cultural knowledge, and adaptability including leadership abilities.